Quantitative proteomics identifies biomarkers to distinguish pulmonary from head and neck squamous cell carcinomas by immunohistochemistry - Annika Richter; Alexander Fichtner; Jasmin Joost; Philipp Brockmeyer; Philipp Kauffmann; Henning Schliephake; Alexander Hammerstein‐Equord; Stefan Kueffer; Henning Urlaub; Thomas Oellerich; Philipp Ströbel; Hanibal Bohnenberger; et al. (Wiley, 2022)
Abstract The differentiation between a pulmonary metastasis and a newly developed squamous cell carcinoma of the lung in patients with prior head and neck squamous cell carcinoma (HNSCC) is difficult due to a lack of biomarkers but is crucially important for the prognosis and therapy of the affected patient. By using high‐resolution mass spectrometry in combination with stable isotope labelling by amino acids in cell culture, we identified 379 proteins that are differentially expressed in squamous cell carcinomas of the lung and the head and neck. Of those, CAV1, CAV2, LGALS1, LGALS7, CK19, and UGDH were tested by immunohistochemistry on 194 tissue samples (98 lung and 96 HNSCCs). The combination of CAV1 and LGALS7 was able to distinguish the origin of the squamous cell carcinoma with high accuracy (area under the curve 0.876). This biomarker panel was tested on a cohort of 12 clinically classified lung tumours of unknown origin after HNSCC. Nine of those tumours were immunohistochemically classifiable.